CAD-based functional therapy during aligner treatment: the “En-Nova”-protocol (technical report) - Segnini, Cristiano; D'Anto, Vincenzo; Valetta, Rosa; Lux, Christopher J.; Roser, Christoph (Seminars in orthodontics, 2025)
Functional orthodontic therapy represents a fundamental element of orthodontic therapy, intending to correct skeletal discrepancies of growing patients by changing their neuromuscular patterns on the long run. To date, consequent functional orthodontic therapy is the first part of a two-phase treatment protocol, which is followed by subsequent dental alignment. For aligners several features are present, which aim to integrate functional therapy into aligner treatment. Examples include inclined planes (“precision wings”) incorporated into the aligners or elastics, both trying to force a mandibular advancement. However, all of them suffer from a rather small skeletal effect, which is why the development of new approaches, which allow for more growth control during aligner therapy, is justified. Against this background, the present article describes a new treatment concept which consists of a CAD-based functional orthodontic appliance overlaying over the aligners during the entire treatment time. By increasing the skeletal control, it is intended to guarantee a consequent functional orthodontic treatment while saving treatment time.